The Effect of Digital Supervision of China Basic Medical Insurance on Out-of-pocket Expenditure: Evidence from Quasi-natural Experiment - Chuncheng Wang PhD; Chen Song MS; Jing Wu PhD; Yanpeng Ning MS; Shuai Wang MS (SAGE Publishing, 2024)
Scientific research has shown that the sustainability of public health insurance is crucial for governments to effectively manage the risks associated with populations aging. In response, the Chinese government has initiated efforts to ensure the long-term viability of its medical insurance funds. This study utilizes data from 24 484 respondents in the 2013, 2015, 2018, and 2020 waves of the China Health and Retirement Longitudinal Study (CHARLS), treating the digital supervision of medical insurance funds as a quasi-natural experiment. The study employs a difference-in-differences (DID) model to evaluate the policy effects and uses heterogeneity analysis to explore variations in impact. The objective is to assess the effectiveness of digital supervision and understand how it achieves its policy goals. The findings indicate that digital supervision of medical insurance funds has a significant positive impact on residents' out-of-pocket medical expenditure. Heterogeneity analysis reveals that the policy's effect is particularly strong in urban samples, especially among younger and elderly urban residents, while showing no significant impact on rural populations. This suggests that the policy has a greater influence on groups with higher moral hazard. By implementing digital supervision of medical insurance funds, the Chinese government has ensured the sustainability of these funds, laying a foundation for mitigating the risks associated with population aging. Additionally, the policy has contributed to promoting healthcare equity and reducing the waste of medical resources.